FORMULATION AND DETERMINATION OF TOTAL FLAVONOID CONTENT OF FACE WASH GEL COCOA FRUIT EXTRACT (THEOBROMA CACAO L.) USING UV-VIS SPECTROPHOTOMETRY - Ahmad Za'im Nabil; Dhina Ayu Susanthi; Mohammad Rofik Usman (LPPM Universitas dr. Soebandi, 2025)
Cosmetic products for skin care have recently been very popular among consumers, especially women. One type of face wash preparation that is used every day is face wash gel, this preparation is very suitable for dealing with facial skin problems. Plants or natural ingredients that can be used to formulate face wash gel preparations are cocoa fruit (Theobroma cacao L.) These compounds can be grouped into secondary metabolite compounds which are biomolecules that are used as new discovery materials in the development of herbal cosmetics. This research aims to formulate a face wash gel preparation and determine the total flavonoid content of the face wash gel from cocoa fruit extract (Theobroma cacao L.). This research uses a laboratory experimental research design by extracting cocoa pods using the maceration method with methanol solvent. Cocoa fruit extract face wash gel was formulated with a concentration of 2.5%, 5%, 7.5%, the formula was tested for the physical properties of the preparation, namely organoleptic test, homogeneity test, spreadability test, foam height test, pH test and viscosity test. Then the total flavonoid content of formula 3 face wash gel was determined using UV-Vis spectrophotometry. The results of the physical properties of the face wash gel preparations with concentrations of 2.5%, 5% and 7.5% met the test parameter requirements, while the results of determining the total flavonoid content of the formula 3 face wash gel received a value of 0.0005/mg/QE/g. Test of the physical properties of the face wash gel preparation from cocoa fruit extract (Theobroma cacao L.) meets the requirements and the face wash gel preparation in formula 3 cocoa fruit extract (Theobroma cacao L.) contains total flavonoid levels of 0.0005/mg/QE/ g.